Analisis Kriminologis terhadap Fenomena Kejahatan Begal dengan Senjata Tajam di Kota Kendari - Kojongian, Rahayu; Anggriyani, Rima (The Juris, 2024)
Motorbike thieves in Kendari City are increasingly disturbing the public, they act without knowing the time or place. The intensity is also increasing sharply. However, there have been no preventative efforts carried out by the police on a large scale to ensure that Kendari is free from the "occupation" of robbers. Almost every day, robberies occur in Kendari and its surroundings. The victims varied, from women, employees, police, TNI, civil servants to journalists. The perpetrators also became more reckless, they began to injure their victims even without putting up any resistance. The phenomenon that recently occurred was that two groups of motorbike thieves were not only looking at their victims' vehicles, but also their possessions such as gold and cash. The research method used is legal research using the juridical-empirical method. This study investigates the factors contributing to the rise of violent theft, particularly in Kendari City. Using a juridical-empirical approach, it examines the implementation of legal provisions in relation to specific instances of theft. Findings suggest that economic, educational, environmental factors, weak law enforcement, and victim negligence play a role in the prevalence of this crime. The study underscores the need for comprehensive measures addressing these factors to enhance security and well-being in Kendari.